2020
DOI: 10.5222/head.2020.02223
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Attitudes Toward Organ Donation and Affecting Factors

Abstract: Aim: This study aimed to determine the attitudes of nursing students regarding organ donation and affecting factors. Methods: This descriptive study comprised a total of 755 nursing students who studied at a university. The total study sample comprised 607 students who agreed to participate. The data were obtained using the personal information and the "Organ Donation Attitude Scale." Data collection tools were filled out by students in classrooms. Data were obtained by number, percentage, average, non-paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition to being a young population, nursing students gain sensitivity in organ donation is very important. It is emphasized in the literature that effective educational program is necessary for university students (12)(13)(14) and specially nursing students (15)(16)(17) to improve attitudes to organ donation. It is necessary to perform studies about raising awareness about organ donation in not only health sciences students but also university students in other fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being a young population, nursing students gain sensitivity in organ donation is very important. It is emphasized in the literature that effective educational program is necessary for university students (12)(13)(14) and specially nursing students (15)(16)(17) to improve attitudes to organ donation. It is necessary to perform studies about raising awareness about organ donation in not only health sciences students but also university students in other fields.…”
Section: Introductionmentioning
confidence: 99%
“…14 In another study with university students, Kavurmacı et al (2014) also reported that 47% of the university students wanted to donate their organs, but that only 4.2% of the students had an organ donor card (12). Several studies performed with nursing students have shown that although high rates of the students had a positive attitude to organ donation, very low rates of the students had an organ donor card (0.4%-4%) (13,16,18,20). Besides, Kavurmacı et al (2014) noted that 74% of the university students did not know how to donate their organs (12).…”
Section: Introductionmentioning
confidence: 99%
“…13 In their study on student nurses in Türkiye, Güler et al found that nurses were hesitant to talk about organ donation. 14 It has been reported in the literature that nurses avoid discussing their knowledge about the effectiveness of organ transplantation with grieving families. [6][7][8]13,15 This study aims to examine the advocacy levels of nurses, who play a key role in informing individ-uals about organ donation, which has never lost its currency and is gaining importance every day, towards organ transplantation and donation.…”
mentioning
confidence: 99%